SMVS: A Web-based application for graphical visualization of malay text corpus - Ahmat Baseri, Noor Bazilah; Abu Bakar, Juhaida; Ahmad, Azizah; Jafferi, Hawa; Zamri, Muhammad Faiz (2020)
Information visualization is an interesting field nowadays. A good information visualization ensures distraction of misleading information is not included in the visualization. Many studies have been conducted on the Quranic corpus. The advancement technology coupled with modern approach of the computer technology can support the learners to understand Qur'an easily. Smart Malay Visualization System (SMVS) is a Python Flask framework web application which help users efficiently to produce the most basic data visualization from a big data. This web application displayed information from the state-of-the-art corpus which is identified through text. Agile development has been adapted to prepare this web application. Six phases of the methodology have been implemented in this study which are requirements, analysis, planning, design, implementation, testing, and deployment. Natural Language Processing approach has been used to visualize the data. Twenty most informative word from each verse has been visualized using Frequency Distribution and has been embedded to the web application. This work focuses on the Malay translation of the Qur'an corpus.